Repercussions faced by health professionals who have experienced the phenomenon of the second victims due to incidents related to patient safety: A scoping review protocol - Elaine Cristine da Conceição Vianna Gonçalves da Costa; Luana Cardoso Pestana; Laríssia Admá de Souza Pereira; Fabrício Glauber Suzano Maciel; Cíntia Silva Fassarella; Renata Eloah de Lucena Ferretti-Rebustini; Cristiane Helena Gallasch (PLoS ONE, 2025)
Introduction: Patient safety is a relevant, timely and globally significant topic. In hospital settings, despite ongoing discussions and advances in patient safety, adverse events continue to occur, impacting not only patients but also healthcare professionals. Health professionals involved in adverse events are considered second victims. This justifies the growing and pertinent interest in the phenomenon of second victim, as this experience affects the competencies and skills of health professionals while influencing their personal livesand general health. Objective: To map and characterize the repercussions experienced by health professionals who have experienced the phenomenon of second victims due to incidents or adverse events related to patient safety in health services. Method: We will conduct a scoping review following the Joanna Briggs Institute’s methodology for scoping reviews, in alignment with the guidelines of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses for Scoping Reviews (PRISMA-ScR) extension. The databases to be searched include PUBMED, SCOPUS, CINAHL, Web of Science (WOS) and LILACS, while the gray literature will be retrieved from the Brazilian Digital Library of Theses and Dissertations (BDTD) and PROQUEST. The identified studies will be compiled and uploaded to EndNote (version X9.3.3), where duplicates will be removed. Two independent reviewers will import the studies into the Rayyan QCR® for organization and selection, with disagreements resolved by a third party. The selection of studies will be based on the population, the concept investigated and the context. The data will be extracted through a pre-established form. Results: The findings will be analyzed in a descriptive and narrative way, aligning the data with the objective of the study and the research question. The data will are presented in tables, diagrams, and graphs containing information from the extraction tool.